2021
DOI: 10.1253/circrep.cr-20-0143
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Effect of Outpatient Cardiac Rehabilitation After Percutaneous Coronary Intervention in Japan

Abstract: very little evidence has been published regarding CR participation rates and the effect of CR on mortality after PCI. The aims of this study were to describe the current participation rates of CR after PCI in ACS and sCAD patients and to investigate the effects of outpatient CR after PCI on the mortality rate using a nationwide administrative database in Japan. Methods Data Source Data were extracted from the National Database of Health Insurance Claims and Specific Health Checkups of Japan (NDB) between April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…In addition, while previous studies in North America reported that men are more likely to participate in CR than women, the present study found no difference between men and women. This finding, however, is consistent with the results of previous studies in Japan 25 , 39 41 . We also found that patients who underwent CABG were more likely to participate in CR than those who underwent PCI, consistent with a previous report 25 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, while previous studies in North America reported that men are more likely to participate in CR than women, the present study found no difference between men and women. This finding, however, is consistent with the results of previous studies in Japan 25 , 39 41 . We also found that patients who underwent CABG were more likely to participate in CR than those who underwent PCI, consistent with a previous report 25 .…”
Section: Discussionsupporting
confidence: 93%
“…The global participation rate for CR following myocardial infarction is less than 30% 13 14. There are regional differences in the proportion of CR participation rates worldwide and in Japan, which suggests that the number of hospitals approved to provide CR and the medical staff may be insufficient to provide adequate CR; strategies to increase the number of CR are required 15 16…”
Section: Discussionmentioning
confidence: 99%
“…It includes claims on inpatient and outpatient services and prescriptions. Japan has a universal health coverage system, and the NDB covers approximately 98% of data on health care services provided by health care institutions, regardless of the type of insurance [ 12 , 13 ]. The NDB includes two anonymized types of personal identification variables (ID1 and ID2) and the group of Nara Medical University has constructed a new patient-matching variable (ID0) with ID1 and ID2, which allows each patient to be followed up longitudinally using an individual claims data system in the NDB database [ 14 ].…”
Section: Methodsmentioning
confidence: 99%